A Robustness Reproduction of "A Systematic Review and Meta-Analysis of 90 Cohort Studies of Social Isolation, Loneliness and Mortality" - Fabio Molo; Samuel Pawel; Gorka Fraga González (Institute for Replication (I4R), 2024)
In a systematic review and meta-analysis, Wang et al. (2023) estimate the association of social isolation or loneliness with mortality outcomes. In their preferred analytical specification, the authors find an increased risk of mortality from all causes for both exposures: a pooled effect size for social isolation of 1.32; 95% confidence interval 1.26 to 1.39; P ﹤ 0.001; a pooled effect size for loneliness of 1.14; 95% CI, 1.08 to 1.20; P ﹤ 0.001. We computationally reproduce these results by extracting data from the article PDF and re-implementing the original analysis, and we compare the extracted data with data that we later received from the authors. Second, we assess the robustness of the main results against plausible alternative analytic choices in three areas: estimation of the random effects models, heterogeneity, and adjustment for publication bias. We find that the main claims of the original authors are robust, although the majority of methods to adjust for publication bias suggest somewhat smaller effects than the original estimates.
Keywords: 330; meta-analysis; computational reproducibility; robustness reproduction